Tracking Physicochemical Conditions of Evaporite Deposition by Stable Magnesium Isotopes: A Case Study of Late Permian Langbeinites. (18th August 2018) - Feng, Chongqin; Gao, Caihong; Yin, Qing‐Zhu; Jacobsen, Benjamin; Renne, Paul R.; Wang, Jun; Chang, Su‐Chin
Abstract: Magnesium isotopic compositions of evaporite deposits may record information concerning brine evolution during deposition. We report Mg isotopic values (δ 26 MgDSM3 ) measured from an evaporite deposit of langbeinite (K2 Mg2 (SO4 )3 ) found in the Permian Salado Formation. We used these data to model Mg isotope fractionation between langbeinite and its parent brine. In addition, both measured and theoretical results are used to estimate precipitation temperature and interpret depositional environment. The Salado langbeinite δ 26 Mg values are relatively low and fall within a relatively narrow range (–4.12 ± 0.03‰ to −3.81 ± 0.07‰). Equilibrium fractionation factors between langbeinite and aqueous Mg 2+ solutions were calculated using quantum chemical density functional theory. All computations were performed at the B3LYP/6‐31 + G(d, p) level. Solvation effects were addressed using a solvent model ("water‐droplet" approach) and mineral structures were investigated using volume variable cluster models (VVCM). The equilibrium Mg isotopic fractionation factors α between langbeinite and model brine solution we obtained are 1.0005, 1.0004, and 1.0003 (Δ 26 Mglangb‐water ≈10 3 lnα = 0.473‰, 0.390‰, and 0.322‰) at 10°C, 25°C, and 40°C, respectively. These relatively large equilibrium fractionation factors indicate significant Mg isotope fractionation between langbeinite and its parent brine during precipitation, as langbeinite preferentially incorporates the heavier 26 Mg and 25 Mg isotopes. Rayleigh distillation modeling of the Salado langbeinite's relatively light Mg isotopic composition requires δ 26 MgDSM3 values of −4‰ for the parent brine. Models favor a precipitation temperature as high as 40°C under equilibrium conditions. Potential disequilibrium precipitation conditions suggested by Mg isotopic data also imply rapid deposition in a hot, arid sedimentary environment prevailing in the southwestern U.S. during the Late Permian. Plain Language Summary: This study, for the first time, reports the Mg isotopic composition of langbeinite, a potassium‐magnesium sulfate evaporite mineral from late Permian. Based on our study, we infer the late Permian seawater, from which langbeinite precipitated, had δ 26 Mg < −4 ‰. Our study demonstrates that Mg isotopic proxies can help constrain temperature conditions and relative rates of evaporation. We describe how Mg isotopes can serve as effective tools for interpreting brine sources and diagenesis. Key Points: This study, for the first time, reports the Mg isotopic composition of langbeinite, a potassium‐magnesium sulfate evaporite mineral from late Permian Based on our study, we infer the late Permian seawater, from which langbeinite precipitated, had δ 26 Mg <–4 ‰ Our study demonstrates that Mg isotopic proxies can help constrain temperature conditions and relative rates of evaporation We describe how Mg isotopes can serve as effective tools for interpreting brine sources and diagenesis